2017
DOI: 10.1590/0034-7167-2017-0103
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of elderly people with chronic kidney disease in conservative treatment

Abstract: Objective:To describe the quality of life (QOL) of elderly people with Chronic Kidney Disease (CKD) in conservative treatment, correlating it with sociodemographic and health-related aspects. Method: This is a quantitative, cross-sectional, and descriptive study that used: a previously validated instrument for data collection; the WHOQOL-BREF and WHOQOL-OLD QOL scales; and the MiniMental State Examination. Results: Thirty-fi ve elderly people (54.30% females), with mean age of 68.26 years, took part in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 22 publications
2
10
0
15
Order By: Relevance
“…Pereria et al studied QOL of elderly CKD patients in particular and observed psychological domain as worst demanding special planning in care. 19 A positive correlation between comorbidities and complications and an inverse correlation between the number of complications and QOL was also n among elderly people with chronic kidney disease in a Brazilian study. 19 Many authors from different regions compared hemodialysis and peritoneal dialysis patients and were of the opinion that PD improved quality of life.…”
Section: Discussionmentioning
confidence: 85%
“…Pereria et al studied QOL of elderly CKD patients in particular and observed psychological domain as worst demanding special planning in care. 19 A positive correlation between comorbidities and complications and an inverse correlation between the number of complications and QOL was also n among elderly people with chronic kidney disease in a Brazilian study. 19 Many authors from different regions compared hemodialysis and peritoneal dialysis patients and were of the opinion that PD improved quality of life.…”
Section: Discussionmentioning
confidence: 85%
“…Regarding age, the result is similar to the recommendation by the Brazilian Society of Cardiology, in which age >55 years old for men and >65 years old for women are considered as a cardiovascular risk factor. A study conducted with elderly patients with a mean age of 68.26 years old who were on conservative treatment at the uremia outpatient clinic in a public hospital showed that 77.1% had high blood pressure as a consequence of chronic kidney disease (6,15) .…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess the QOL in adults, the World Health Organization Quality of Life (WHOQOL-bref) was used, with 26 assertions divided into four domains: physical (items: 3, 4, 10, 15, 16, 17, and 18 ), psychological (items: 5, 6, 7, 11, 19, and 26), social relations (items: 20, 21, and 22), and environment (items: 8, 9, 12, 13, 14, 23, 24, and 25), in addition to 2 general assertions of QOL (items 1 and 2), which correspond to the 24 facets of the original WHOQOL (14), 2000 [13][14][15] .…”
Section: Introduction Methodsmentioning
confidence: 99%
“…The researchers were trained to administer the questionnaires to avoid possible inconsistencies in data collection, although the instruments used in the study were composed of self-report items. The preparation of the data After identifying the emotional state of the child, the items were read out to them, and they indicated their response, ranging from 0 to 3 (very unhappy, unhappy, happy, and very happy, respectively); a final score is calculated with the sum of scores on each question 13 .…”
Section: Introduction Methodsmentioning
confidence: 99%